Review of tools of cardiovascular disease risk stratification: interpretation, customisation and application in clinical practice - Chia, Y.C. (Singapore Medical Association, 2011)
Cardiovascular Disease (CVD) is the leading cause of death in both developed and developing countries. While it is relatively easy to identify those who are obviously at high risk and those at the lowest risk for CVD, it is often the large group of individuals with what appears to be modestly abnormal risk factors who contributes most to the burden of CVD. This is where estimation of CVD risk is necessary. Many tools for risk assessment have been devised. All these risk scores have their own inherent advantages and disadvantages. Furthermore, they may also not be directly applicable to a local population. Ideally, each country should have its own risk score that takes into account other factors as well. In the interim, it is worthwhile to be familiar with one of these scores, select one that is most appropriate for your patient and discuss treatment options based on the estimated risk.